Low Liver Density Is Linked to Cardiovascular Comorbidity in COPD: An ECLIPSE Cohort Analysis - Viglino D; Martin M; Almeras N; Després JP; Coxson HO; Pépin JL; Vivodtzev I; Maltais F (International Journal of COPD, 2020)
Damien Viglino,1,2,* Mickaël Martin,1,* Natalie Almeras,1 Jean-Pierre Després,1 Harvey O Coxson,3 Jean-Louis Pépin,2 Isabelle Vivodtzev,2 François Maltais1 On behalf of the Evaluation of COPD Longitudinally to Identify Predictive Surrogate Endpoints (ECLIPSE) investigators1Centre de Recherche, Institut Universitaire de Cardiologie et de Pneumologie de Québec-Université Laval, Québec, Canada; 2Hypoxia Pathophysiology Laboratory INSERM U1042, Grenoble Alpes University Hospital, Grenoble, France; 3Radiology, University of British Columbia, Vancouver, British Columbia, Canada*These authors contributed equally to this workCorrespondence: Damien ViglinoCentre de Recherche Institut Universitaire de Cardiologie et de Pneumologie de Québec, 2725 Chemin Sainte-Foy, Québec, QC G1V 4G5, CanadaTel +1 418 656 8711Email damien.viglino.1@ulaval.caPurpose: Fatty liver disease is associated with cardiometabolic disorders and represents a potential key comorbidity in Chronic Obstructive Pulmonary Disease (COPD). Some intermediary mechanisms of fatty liver disease (including its histological component steatosis) include tissue hypoxia, low-grade inflammation and oxidative stress that are key features of COPD. Despite these shared physiological pathways, the effect of COPD on the prevalence of hepatic steatosis, and the association between hepatic steatosis and comorbidities in this population remain unclear. Liver density measured by computed tomography (CT)-scan is a non-invasive surrogate of fat infiltration, with lower liver densities reflecting more fat infiltration and a liver density of 40 Hounsfield Units (HU) corresponding to a severe 30% fat infiltration.Patients and Methods: We took advantage of the international cohort ECLIPSE in which non-enhanced chest CT-scans were obtained in 1554 patients with COPD and 387 healthy controls to analyse the liver density at T12-L1.Results: The distribution of liver density was similar and the prevalence of severe steatosis (densitya=1.59, 95% CI 1.12 to 2.24) and stroke (ORa=2.20, 95% CI 1.07 to 4.50), in comparison with the highest liver density quartile.Conclusion: The present data indicate that a low liver density emerged as a predictor of cardiovascular comorbidities in the COPD population. However, the distribution of liver density and the prevalence of severe steatosis were similar in patients with COPD and control subjects.Keywords: chronic obstructive pulmonary disease, liver density, steatosis, fatty liver disease, chest CT-scan, cardiovascular comorbidity, ECLIPSE